A educação popular e o campo das práticas socioeducativas: considerações sobre a história da educação popular e de seus desafios atuais - Luís Antonio Groppo; Suzana Costa Coutinho (EccoS – Revista Científica)
Through literature review and reflection on the current characteristics of popular education in Brazil, one realizes the historical importance of popular education for the formation of the field of socio-educative practices. However, the principles of popular education - dialogue, struggle for liberation and diversity - are quite subverted when this field is consolidated. The recovery of the historical trajectory of popular education emphasizes its origins in the time of populism, its relationship to social movements, his participation in the struggle against the dictatorship and the challenges imposed since the late twentieth century. This recovery of the history and principles of popular education movements aims to inspire educators dissatisfied with the current direction of the field where they belong, to live and to propose creative heterodoxies.